2015
DOI: 10.15537/smj.2015.12.12345
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ventilator-associated pneumonia and ventilator-associated tracheobronchitis in the intensive care unit

Abstract: Objectives:To assess current practices of different healthcare providers for treating extensively drug-resistant (XDR) Acinetobacter baumannii (AB) infections in tertiary-care centers in Saudi Arabia.Methods:This cross-sectional study was performed in tertiary-care centers of Saudi Arabia between March and June 2014. A questionnaire consisting of 3 parts (respondent characteristics; case scenarios on ventilator-associated pneumonia [VAP] and tracheobronchitis [VAT], and antibiotic choices in each scenario) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Therefore, medical devices such as humidifiers, intubation tubes, and ventilators are important sources for nosocomial infections caused by Chryseobacterium spp [1] , [13] . VAP incidence is estimated to be 10–25% in Saudi Arabia and is associated with 25–50% mortality rates of these cases [14] . Environmental and mechanical ventilator samples did not grow any C .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, medical devices such as humidifiers, intubation tubes, and ventilators are important sources for nosocomial infections caused by Chryseobacterium spp [1] , [13] . VAP incidence is estimated to be 10–25% in Saudi Arabia and is associated with 25–50% mortality rates of these cases [14] . Environmental and mechanical ventilator samples did not grow any C .…”
Section: Discussionmentioning
confidence: 99%
“…[11] Kumar et al [26] reported that delay in antibiotic treatment, especially in patients with septic shock, was associated with increased mortality. In a survey conducted by Al-Omari et al, [27] more than 50% of the participants reported that they preferred to start empirical intravenous colistin in the presence of septic shock in late-onset VAP patients. In our study, intensive care mortality and septic shock rates were higher in VAP cases, although in other studies they were similar.…”
Section: Discussionmentioning
confidence: 99%
“…The IDSA guidelines recommend against the routine use of colistin in treating VAP while European guidelines similarly state the empiric therapy to be guided by the mortality risk, local ecology, and other MDR selection risk factors [ 10 , 22 ]. Yet, colistin-based combination therapy is still used in some critical care centers to empirically treat XDR pathogens [ 43 ]. Less common VAP bacterial pathogens include Stenotrophomonas maltophilia , Burkholderia cepacia , Legionella , and anaerobes which are known for their intrinsic resistance to multiple antimicrobial classes [ 44 , 45 ].…”
Section: Microbiology In Vapmentioning
confidence: 99%